Do urinary mast cell mediators predict immune response to BCG in patients with primary high‐grade non‐muscle invasive bladder cancer?. Issue 5 (5th January 2021) - Simsekoglu, Muhammed Fatih; Kaleler, Islim; Onal, Bulent; Demirdag, Cetin; Citgez, Sinharib; Uslu, Ezel; Erozenci, Ahmet; Talat, Zubeyr
Abstract: Background: Mast cells play a critical role in cancer‐associated immunity. We aimed to determine the predictive value of urinary mast cell mediators in patients with non‐muscle invasive bladder cancer (NMIBC) treated with Bacillus Calmette‐Guérin (BCG) immunotherapy. Methods: In this prospective study, 19 patients who received immunotherapy because of NMIBC (Group 1) and 19 healthy participants (Group 2) were enrolled. Urine samples were collected to assay N‐methylhistamine, histamine, and tryptase levels immediately before the first BCG instillation, immediately after the third and sixth instillations, and 4 weeks after the sixth instillation in Group 1 and at a single visit in Group 2. The changes in urinary markers because of BCC response, BCG instillation, and the presence of NMIBC were assessed. Results: The average age was 56.1 ± 10.5 years in Group 1 and 52.6 ± 9.7 years in Group 2. Fourteen patients had high‐grade Ta tumours and five had T1 tumours. While 12 patients had responded to the BCG, seven patients did not respond to the BCG. There was no correlation between mast cell mediators and BCG response. The N‐methylhistamine and histamine levels significantly increased with the onset of immunotherapy, and N‐methylhistamine levels significantly decreased when immunotherapy was terminated ( P  < .05). The pre‐BCG estimated marginal mean values of N‐methylhistamine were significantly higher in Group 1 than in Group 2 ( P  < .05). Conclusions: Our study is the first to identify the changes in mast cell mediators with the onset of immunotherapy and in presence of bladder cancer. However, these mediators cannot predict patients' response to immunotherapy.